2014
DOI: 10.1080/03634523.2014.978800
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Role of Self-Disclosure and Connectedness in the Process of Instructional Dissent: A Test of the Instructional Beliefs Model

Abstract: The current study examined the relationship between student-to-student communicative behaviors and communication outcomes in the college classroom. The instructional beliefs model was used to examine student self-disclosures, student perceptions of connectedness, and student enactment of instructional dissent. Students (N = 351) completed questionnaires assessing their perceptions of other students' self-disclosures, classroom connectedness, and their own enactment of expressive, rhetorical, and vengeful disse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 49 publications
(89 reference statements)
1
8
0
Order By: Relevance
“…The identification of associations between CCC and four technological factors (advanced computer self-efficacy, Internet and entertainment computer experience, program and software computer experience, and computer importance) contributes new knowledge for researchers and practitioners. These associations should be considered for improving students’ CCC, which is recognized as important in both traditional face-to-face (e.g., Johnson & LaBelle, 2015; Sidelinger et al., 2011; Sollitto et al., 2013) and computer-mediated environments (e.g., Xu et al, 2016; Ritter et al., 2010). Most significantly, online environments impose many additional communication challenges (Rovai & Jordan, 2004; Walther, 1992), and our findings provide some insights useful to addressing what Ritter et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of associations between CCC and four technological factors (advanced computer self-efficacy, Internet and entertainment computer experience, program and software computer experience, and computer importance) contributes new knowledge for researchers and practitioners. These associations should be considered for improving students’ CCC, which is recognized as important in both traditional face-to-face (e.g., Johnson & LaBelle, 2015; Sidelinger et al., 2011; Sollitto et al., 2013) and computer-mediated environments (e.g., Xu et al, 2016; Ritter et al., 2010). Most significantly, online environments impose many additional communication challenges (Rovai & Jordan, 2004; Walther, 1992), and our findings provide some insights useful to addressing what Ritter et al.…”
Section: Discussionmentioning
confidence: 99%
“…Information peers were significantly less connected than other peer types, but there was no significant difference between the three peer types and familiarity with teacher. Johnson and LaBelle (2015) examined an instructional beliefs model for expressive dissent. Findings suggested the amount, relevance, and negativity of peer self-disclosures effected students’ CCC.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…There is considerable evidence that CCC is positively related to students’ participation (Fassinger, 1996, 1997; Sidelinger & Booth-Butterfield, 2010) and learning (Frisby & Martin, 2010; Johnson, 2009; Sidelinger & Booth-Butterfield, 2010) in face-to-face educational environments. In addition, some research has suggested that CCC is related to classroom assimilation (Johnson & LaBelle, 2015) and that an instructor’s presence may not be directly associated with it (Frisby & Martin, 2010; Sidelinger, Bolen, Frisby, & McMullen, 2011). This notion has been empirically supported in comparative studies exploring face-to-face and blended learning instructional delivery methods (e.g., Ritter, Polnick, Fink, & Oescher, 2010; Xu, Yang, & MacLeod, in press).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Second-order variables can include students' expectations of their academic success, their control of learning beliefs, their learner empowerment, and their academic self-efficacy (Weber et al, 2011). The third-order constructs include student learning outcomes (Johnson & LaBelle, 2015), which can be comprised of cognitive (i.e., acquisition and understanding of knowledge), affective (i.e., change in students' attitude and feelings toward content), and behavioral (i.e., activities and student behaviors that indicate learning) learning (Weber et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the fifth study, Johnson and LaBelle (2015) examined the relationship between instructor behaviors and learning outcomes. The first-order construct was instructor selfdisclosure (i.e., amount, relevance, and negativity), the second-order construct was student classroom connectedness, and the third-order construct was student dissent (i.e., rhetorical, expressive, and vengeful).…”
Section: Introductionmentioning
confidence: 99%